Descriptive study of marine debris at Pantai Cempaka, Kuantan, Pahang - Abdullah Sani, Siti Hajar; Ruslai, Nurulhidayati; Mohd. Sani, Rositi Mashani; Zahari, Shafiyyah Solehah (Centre of Foundation Studies (CFS), IIUM, 2024)
Pantai Cempaka is a recreational beach within a small fishing village in Kuantan, Pahang. It is also a natural habitat for various flora such as mangrove trees. Mangrove trees grow best in brackish water particularly requiring an area free from pollutants such as marine debris. Any persistent, manufactured, or processed solid material discarded, disposed or abandoned in the marine and coastal environment is defined as marine debris. Aligned with Sustainable Development Goal (SDG) 12: Responsible Consumption and Production which aims to focus on environmentally sound management of all wastes, the Biology Department initiated a waste analysis via a beach clean-up program covering 3,317.38 m2 of the study area involving 19 staff and 45 biological sciences students from Centre for Foundation Studies, International Islamic University Malaysia (CFS IIUM). The program aspires to educate the participants on the importance of biodiversity and ecosystems and instil awareness of a sustainable environment. This research was conducted to determine the type and amount of marine debris. The collected marine debris were identified, sorted based on category, counted, and weighed. Seven categories of marine debris are plastic, rubber, glass and ceramic, cloth, wood and timber, metal, and paper cardboard. A total of 3,144 items were found with a total weight of 275.18 kilograms. The results showed that plastic debris was the major contributor to beach pollution (93.2%), followed by rubber (4.4%), and glass and ceramic (2.4%). Plastic debris weighed the most (224.79 kg), rubber (26.50 kg), and glass and ceramic (23.89 kg). In conclusion, our findings show similar results to those previous studies on marine debris conducted in Malaysia, indicating that plastic is the most abundant debris observed.